2017
DOI: 10.1038/s41598-017-02553-y
|View full text |Cite
|
Sign up to set email alerts
|

Low level of Lck kinase in Th2 cells limits expression of CD4 co-receptor and S73 phosphorylation of transcription factor c-Jun

Abstract: The Src-family tyrosine kinase Lck is an enzyme associated with the CD4 and CD8 co-receptors and promoting signaling through the T cell receptor (TCR) complex. The levels of Lck expression and activity change during the development and differentiation of T cells. Here we show that Lck expression is higher in Th1 cells as compared to Th2 cells. Ectopic overexpression of Lck in Th2 cells results in increased expression of CD4 co-receptor and enhanced S73 phosphorylation of transcription factor c-Jun. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The Src-family tyrosine kinase Lck is associated with the CD4 and CD8 co-receptors. Lck expression is reduced in Th2 cells compared Th1 cells; Ectopic expression of Lck in Th2 cells led to increased expression of CD4 co-receptor and c-Jun phosphorylation at Serine 73 via concerted actions of JNK and ERK signaling [49], suggesting that Lck promotes Th1 polarization in part through a JNK-dependent process. JNK/c-Jun signaling is at least partly responsible for CD27-induced suppression of IL-17 and CCR6 expression and consequently reduced Th17 cell development and differentiation [50].…”
Section: Jnk Regulation Of Immune Responsesmentioning
confidence: 95%
See 1 more Smart Citation
“…The Src-family tyrosine kinase Lck is associated with the CD4 and CD8 co-receptors. Lck expression is reduced in Th2 cells compared Th1 cells; Ectopic expression of Lck in Th2 cells led to increased expression of CD4 co-receptor and c-Jun phosphorylation at Serine 73 via concerted actions of JNK and ERK signaling [49], suggesting that Lck promotes Th1 polarization in part through a JNK-dependent process. JNK/c-Jun signaling is at least partly responsible for CD27-induced suppression of IL-17 and CCR6 expression and consequently reduced Th17 cell development and differentiation [50].…”
Section: Jnk Regulation Of Immune Responsesmentioning
confidence: 95%
“…Taken together, JNK mediates keratinocyte cell production and the release of chemokines and cytokines, leading to the recruitment of immune cells. These immune cells stimulate further dysregulation of skin cell proliferation and the continued amplification of the disease state [49,50,[69][70][71][72][73] (Figure 3).…”
Section: Jnk Regulation Of Barrier Protein Defectsmentioning
confidence: 99%
“…For the in vitro study, PBMCs from RA patients were collected after incubating with IgD and IgD-Fc-Ig for 48 h. Cells were lysed in lysis buffer supplemented with protease inhibitors and phosphatase inhibitors for 30 min on ice (24), whereas for the in vivo study, mice spleens were isolated from each group and homogenized in lysis buffer. Primary antibodies Lck (1:1,000), p-Lck (1:1,000), ZAP70 (1:1,000), p-ZAP70 (1:1,000), and βactin (1:1,000) were then incubated at 4 • C overnight, and a goat anti-rabbit secondary antibody (1:50,000) was incubated for 2 h at 37 • C. The membrane was scanned using GS-700 Imaging Densitometer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…LCK exists in all normal T cells. In the cells, LCK is located in the plasma membrane and vesicles around the centrosome, which is related to the cytoplasmic tail of CD4 co-receptors on helper T cells and CD8 co-receptors on cytotoxic T cells, to help T-cell receptor (TCR) complexes signal and participate in the TCR-mediated T-cell activation ( Shebzukhov et al, 2017 ). Human somatic cell experiments showed that the inhibition of LCK expression led to the inhibition of the TCR pathway, thereby hindering the differentiation and development of T cells.…”
Section: Discussionmentioning
confidence: 99%